Stories from the East: COVID-19 Situation in India - Rebecca Jane Joseph; Hooi-Leng Ser (Progress in Microbes and Molecular Biology)
The war against COVID-19 is still ongoing since the first report in December 2019. On 1st May 2021, India has reported over 400,000 new COVID-19 cases within 24 hours. The situation in the country continued to progress, which was associated with the reporting of the variant-of-concern and the variant-of-interest, including the B1.617 viruses. The government has taken public health measures, including campaigns to increase awareness about mask-wearing and physical distancing as well as lockdown plans to prevent further spread of the disease in the densely populated country. Furthermore, the countrywide vaccination program has begun in early 2021, while the government of India continues to monitor the COVID-19 situation in the country. The current review aims to provide a brief situation report in India before discussing management strategies taken and different phases of the vaccination program.